IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO DALAM PENDIDIKAN PADA ORGANISASI PENDIDIKAN DI ERA DIGITAL - Darmawan Rahmadi; Khairul Tri Anjani (Nusantara Hasana Journal, 2024)
This study aims to investigate the implementation of the ISO Quality Management System in educational organizations, focusing on the aspects of establishment, implementation, evaluation, control, and improvement (PEPP). The research method used is a case study with a qualitative approach. Data were collected through observation, interviews, and document analysis. The results of the study indicate that the implementation of the ISO Quality Management System has brought significant changes in the management of educational organizations. The steps of establishing quality standards, implementing established procedures, periodic evaluations, controlling processes, and continuous improvement efforts have increased the efficiency and effectiveness of education. However, there are challenges in integrating all elements into a unified whole. Recommendations are given to educational organizations to further strengthen the implementation of the ISO Quality Management System by paying attention to aspects that still need to be improved. The use of technology in the quality management process needs to be improved to optimize efficiency and accessibility of information. In addition, it is necessary to increase awareness and commitment of all members of the organization towards the importance of quality management in achieving educational goals.